BODY AS A FACTOR OF INDIVIDUALIZATION OF PHYSICAL EDUCATION LESSONS OF UNIVERSITY STUDENTS - Bushma, T.V.; Mironova, O.V.; Sharonova, A.V.; Bondarchuk, I.L. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to development and approbation of means of physical culture in the interests of increasing the level of physical fitness of students, depending on the type of physique. Methods and structure of the study. The development was carried out on the basis of three universities in the period from 2020 to 2021 St. Petersburg and the Leningrad region. In the course of the work, indicators of physical development, physical fitness of the contingent and body types of students (230 people) were determined according to the traditional method. Constant monitoring of indicators of physical fitness, attendance and motivation for physical culture and sports was carried out. Results and conclusions. As a result of the development, the method of individualization of physical culture classes of students based on their typological characteristics was substantiated and tested, which contributed to an increase in the level of physical fitness and had a positive effect on the effectiveness of the process. The result is a pronounced effect of the program on students of the hypersthenic type, which is reflected in a greater percentage of satisfactory results when passing control exercises compared to other typological groups.